Effect of alkyl derivatization of gellan gum during the fabrication of electrospun membranes. Issue 2 (June 2022) - Palumbo, Fabio Salvatore; Federico, Salvatore; Pitarresi, Giovanna; Fiorica, Calogero; Scaffaro, Roberto; Maio, Andrea; Gulino, Emmanuel Fortunato; Giammona, Gaetano
Electrospun nanofibers based on polysaccharides represent a consolidated approach in Tissue Engineering and Regenerative Medicine (TERM) and nanomedicine as a drug delivery system (DDS). In this work, two chemical derivatives of a low molecular weight gellan gum (96.7 kDa) with aliphatic pendant tails were processed by electrospinning technique into non-woven nanofibrous mats. In order to generate spinnable blends, it was necessary to associate poly vinyl alcohol (PVA). The relationships between the physicochemical properties and the processability via electrospinning technique of gellan gum alkyl derivatives (GG-C8 and GG-C12 having a degree of alkyl chain derivatization of 17 mol % and 18 mol %, respectively) were investigated. The deposition of nanometric fibers (212.4 nm ± 60.0) was achieved by using the blend GG-C8 /PVA spinned at 5% w/v in water. The use of a binary solvent composed of water and ethanol in a volumetric ratio 95:5 improved further spinnability obtaining similar nanofiber diameters (218.0 nm ± 96.0). The rheological analysis has allowed to highlight the role of the alkyl portion (C8 and C12 ) on the spinnability of the blended polymers.